2011
DOI: 10.1111/j.1365-2109.2010.02766.x
|View full text |Cite
|
Sign up to set email alerts
|

Marine wax ester digestion in salmonid fish: a review

Abstract: Alternative marine resources from lower trophic levels could partly cover the rapidly increasing needs for marine proteins and oils in the future. The North Atlantic calanoid copepod, Calanus ¢nmarchicus, has a high level of lipids rich in n-3 fatty acids. However, these animals have wax esters as the main lipid storage component rather than triacylglycerol (TAG). Although these esters are considered di⁄cult to digest by many ¢sh, is it well known that juvenile Atlantic salmon (Salmo salar) feed on zooplankton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 104 publications
(207 reference statements)
0
16
0
Order By: Relevance
“…The use of calanus oil as lipid sources for salmon feed has also been intensively studied [ 91 ]. Salmon has a limited ability to digest wax esters, and these lipids should not exceed 30% of the dietary lipid, so the high amount of wax ester in some of the mesopelagic species has to be taken into account when used for fish feed [ 84 , 92 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of calanus oil as lipid sources for salmon feed has also been intensively studied [ 91 ]. Salmon has a limited ability to digest wax esters, and these lipids should not exceed 30% of the dietary lipid, so the high amount of wax ester in some of the mesopelagic species has to be taken into account when used for fish feed [ 84 , 92 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…CO is, however, distinct from other marine oils in that long-chain fatty alcohols are attached to (n-3) PUFA as wax esters. A large proportion of fatty alcohols are found as monounsaturated 20:1(n-9) and 22:1 (n-11) alcohols (5), which may be oxidized to MUFA during digestion (6). Beside its large amounts of EPA and DHA, CO is an abundant source of 18:4(n-3) (SDA), which may function as a precursor for biosynthesis of EPA and DHA in mammals (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to digest wax esters appears to vary across vertebrate species: two species of baleen whales [4,9] and certain seabirds were reported to be highly efficient,~90% and 85%, respectively, whereas rats and dogs were less efficient, 50% and 10%, respectively [8,52]. Wax esters hydrolyze at a slow rate, up to 25 times slower than triglycerides in multiple species of marine fish [6,7,[53][54][55][56], due, in part, to their high degree of hydrophobicity. Studies on wax ester digestion in fish and seabirds suggested increased retention time of wax esters in the GI tract is one factor that may be necessary for increased hydrolysis of wax esters [55,57].…”
Section: Wax Ester Digestion and Major Changes To Microbes In The Smamentioning
confidence: 99%
“…Moreover, the overall composition of the wax ester pool in the colon was significantly different from that of the stomach chambers, and yet all wax esters species in the colon were also observed in the stomachs, suggesting that the wax esters remaining in the colons represented undigested dietary wax esters. Wax ester digestibility, and the bioavailability of their hydrolytic products, may depend on a number of factors: the quantity of wax esters consumed, the quantity of triglycerides consumed with the wax esters, the concentration of bile salts (it has been proposed that triglycerides and bile salts both may improve the solubility of the highly hydrophobic wax esters), mechanisms for mixing, retention time, and/or chemical structure of the wax esters (chain length or degree of saturation) [52,53,55]. Given the correlation between wax esters and the microbiotas we observed in the jejunum (mid-small intestine) of bowhead whales, the presence or absence of certain microorganisms in the small intestine might also affect wax ester digestion and thus, the abundance of wax esters in the colon.…”
Section: Diversification Of Microbes Coincides With Reduced Prey Lipimentioning
confidence: 99%